DARI HEALING HINGGA FLEXING: KAJIAN SEMANTIK TERHADAP ISTILAH POPULER GENERASI Z DI MEDIA SOSIAL - Anwar; Liyana Dian Prastiwi; Henry Trias Puguh Jatmiko (Indonesian language and literature education program Majapahit Islamic University, 2026)
This study aims to describe the forms of semantic shift in the popular term ‘Generation Z’ on social media. The study employs a qualitative descriptive method with a semantic approach. Data were collected from posts, captions, comments and conversations on the TikTok, Instagram and X platforms using the ‘listen, observe, engage and discuss’ (LOED) technique and note-taking. The data were analysed using the interactive analysis model developed by Miles, Huberman and Saldaña, comprising the stages of data reduction, data presentation and drawing conclusions. The research findings indicate that the popular term ‘Generation Z’ can be grouped into four categories, namely lexical meaning, contextual meaning, shifts in meaning, and loanwords. The most prevalent forms of semantic change include semantic extension, metaphorisation, and changes in connotation. Furthermore, the predominance of loanwords from English demonstrates the strong influence of global digital culture on the development of the Indonesian lexicon. Social media serves as the primary space for the formation, dissemination and adaptation of new meanings, which are used by Generation Z as a means of communication, expression of identity and social evaluation. This study demonstrates that linguistic dynamics in the digital age unfold rapidly, creatively and contextually, thereby enriching the study of the semantics of contemporary Indonesian. Keywords: Semantics, shift in meaning, Generation Z, social media